Deciphering FFAR4 Mediated Functional Pathways and Potential Drug Targets in Diabetes Mellitus: An Integrated Protein Interaction Network Analysis and Kinetic Simulation (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Type 2 Diabetes is a metabolic disorder that affects people worldwide. The G-protein coupled receptor (GPCR) known as free fatty acid receptor 4 (FFAR4) has been shown to be a potential therapeutic target for type 2 diabetes mellitus (T2DM)and complications linked to obesity. The present study focuses on the pharmaceutical role of FFAR4 and its potential agonists by predicting anti-diabetic responses, including insulin secretion, glucose uptake and calcium ion concentration levels. We identified differentially expressed genes and elucidated their role extensively through analysis of pathways, molecular mechanisms and linked biological processes. In the present study, a systems biology approach was implemented to establish an interaction network between FFAR4 and its driver’s such as CASR and NR1H4, that highlighted their significance as potential prognostic and therapeutic targets. A mathematical model incorporating biological events mediated by these proteins is studied and simulated using kinetics law reactions. Furthermore, the kinetic simulations were conducted to assess the impact of drug molecules, namely comp35, comp50, compN1 and compN2, on FFAR4 function. The findings reveal FFAR4’s potential as a therapeutic target for the treatment of type 2 diabetes mellitus.